PENGARUH RETURN ON EQUITY RATIO (ROE), DEBT TO EQUITY RATIO (DER), DAN EARNING PER SHARE RATIO (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD & BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Mulia, Safara; Mursidah; Yunita, Nur Afni; Mardiaton; Yunina; Indrayani (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of Return On Equity (ROE), Debt To Equity Ratio (DER), and Earning Per Share (EPS) on stock prices of Food & Beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research employs a quantitative approach using secondary data obtained from annual financial statements. Data were analyzed using panel data regression with EViews 12 software. The results indicate that Return On Equity (ROE) has a negative and insignificant effect on stock prices, Debt To Equity Ratio (DER) also has a negative and insignificant. effect, while Earning Per Share (EPS) has a positive and significant effect on stock prices. These findings suggest that EPS serves as a key indicator for investors in assessing company performance and profitability potential.